Fibrinogen-Albumin Ratio: An Independent Recurrence Factor for Colorectal Cancer Stages II and III in a Competing Risk Model - Michiaki Shimada; Takanori Goi; Takayuki Tagai; Katsuzi Sawai; Mitsuhiro Morikawa; Masato Tamaki; Kenji Koneri (Journal of the Anus, Rectum and Colon)
Objectives: Colorectal cancer remains a major global health concern. Identifying high-risk patients is crucial for optimizing treatment strategies. The prognostic value of biomarkers, especially considering competing risks, remains unclear. We used a competing risks model to exclude the influence of non-cancer-related mortality and examined FAR as a predictor of recurrence in colorectal cancer. Methods: This retrospective study analyzed 359 patients with stage II or III colorectal cancer from the cecum to the oral side of the peritoneal inversion, all of whom underwent curative resection at Fukui University Hospital. The primary outcome was cancer recurrence. The fibrinogen-albumin ratio (FAR) was assessed using univariate and multivariate analyses, including competing risk models, with a cutoff value of >0.131. Results: Univariate analysis identified factors significantly associated with poorer outcomes, including T4 stage, gross appearance type 3/4/5 tumors, stage III disease, elevated neutrophil-to-lymphocyte ratio, prognostic nutritional index, carcinoembryonic antigen, and FAR. Multivariate analysis confirmed FAR as an independent prognostic factor. A predictive model combining FAR, stage III disease, and T4 stage demonstrated the best performance based on Akaike information criterion and Bayesian information criterion values. Conclusions: FAR is a robust prognostic biomarker for colorectal cancer. Incorporating FAR into clinical practice may enable healthcare providers to more accurately stratify high-risk patients, facilitating personalized treatment strategies.